The gaps in satisfaction with transit services among BRT, metro, and bus riders: Evidence from Guangzhou - Cao, Jason; Cao, Xiaoshu; Zhang, Chen; Huang, Xiaoyan (Journal of Transport and Land Use, 2015)
This paper explores transit riders’ satisfaction with bus rapid transit (BRT) and compares BRT with conventional bus and metro services using revealed preference data from Guangzhou, China. A trivariate ordered probit model is developed to examine the effects of various service attributes on riders’ overall satisfactions with the three types of transit. We find that the top-three influential attributes for satisfaction with BRT are ease of use, safety while riding, and comfort while waiting. Moreover, transit riders are most satisfied with metro, followed by BRT and conventional bus. The top-five attributes that contribute to the difference in the overall satisfaction between BRT and metro are ease of use, comfort while riding, convenience of service, travel time, and comfort while waiting. Based on the findings, we propose specific strategies that can be used to enhance BRT quality of service.